Changes and challenges to international forestry: preparing for the 21st century - Vanclay, J.K. (1997)
Recent and anticipated changes in technology and institutions offer renewed challenges for forestry in Australia and abroad. Accommodating change is easy when it is foreseen, but when change is unheralded it may be best managed by those with broad experience and current knowledge. Thus we may prepare for change through selected refresher courses and by actively looking to broaden our experience. It is likely that Australia's role regionally and globally as a seat of learning, as a genetic storehouse and as timber trader will become more important in the future. Australia and New Zealand have much expertise and experience that may be sought by our near northern neighbours, especially in reduced impact logging, research management and conservation planning.